2017
DOI: 10.1002/mus.25482
|View full text |Cite
|
Sign up to set email alerts
|

Physical function and mobility in children with congenital myotonic dystrophy

Abstract: Introduction Congenital Myotonic Dystrophy (CDM) occurs when symptoms of myotonic dystrophy present at birth. This study evaluated the relationship between physical function, muscle mass, and age to provide an assessment of the disease and help prepare for therapeutic trials. Methods CDM participants performed timed functional tests (TFTs), The first 2 minutes of the 6-minute walk test (2/6MWT), myometry, and dual-energy x-ray absorption (DEXA) scans. Healthy controls (HC) performed TFTs, 6MWT, and myometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
3
11
0
5
Order By: Relevance
“…In conclusion, in follow‐up to our previous work in which we showed that DXA measures of regional muscle mass correlate well with motor strength and function testing, we now show that the muscle mass of patients with CDM improves almost to normal compared with healthy, age‐matched controls. This corresponds to what is seen clinically in children with CDM over time.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In conclusion, in follow‐up to our previous work in which we showed that DXA measures of regional muscle mass correlate well with motor strength and function testing, we now show that the muscle mass of patients with CDM improves almost to normal compared with healthy, age‐matched controls. This corresponds to what is seen clinically in children with CDM over time.…”
Section: Discussionsupporting
confidence: 79%
“…The measurement of LBM has the potential to be an important biomarker to reflect muscle mass and, ultimately, functional strength in this population. As a surrogate for muscle strength, it appears to have some value as it correlated well with functional measures such as the 6‐minute walk test and 10‐meter walk/run test in a previous study by our group; where we also demonstrated that older children have higher muscle mass, however, we did not compare this improved muscle mass to age‐matched controls or typically developing children …”
mentioning
confidence: 71%
See 3 more Smart Citations